(untitled) (Research, Society and Development, 2021)
Considered a complex ecosystem, the Atlantic Forest holds one of the largest biodiversities on the planet. Studies in watersheds inserted in this ecosystem are relevant to understand its hydrological functioning, aiming to monitor the quantity and quality of water arising from the use of natural resources. In turn, the morphometric, physicochemical, and microbiological characteristics of the water in watersheds were of great interest to compose the object of this study, since the quality of this environmental service reflects directly on the health of the population and the aquatic system. The current research was conducted in the Prata watershed, situated within the limits of the Dois Irmãos State Park, a remnant of the Atlantic Forest, located in the Metropolitan Region of Recife (RMR). In order to characterize the morphometry and relate physical-chemical and microbiological aspects of the water with the anthropic actions acting on the Prata watershed, it was verified that the drainage network is of 4th order and presents a low tendency to flooding and if they occur they can be of medium to large size. There is a predominance of the 20 - 45% slope class, totaling almost 50% of the micro-basin area. During the monitored period the quality of the water in the two reservoirs was outside the potability standards, requiring disinfection treatment for consumption. It is necessary to take measures of protection and environmental education of the surrounding communities in order to mitigate the advance of anthropic pressure on the Prata watershed area.